A Theoretical Evaluation of the Behavior of Nitrosoamidine upon Reacting with Methoxy Butadiene as Potential Heterodiene or Heterodienophile - Hamzehloueian, Mahshid; Haghdadi, Mina; Lotfi, Marjan (Letters in Organic Chemistry, 2022)
The molecular mechanism of experimentally observed regio- and chemo-selectivity of the cycloaddition reaction of nitrosoamidine 1 and 1-methoxy butadiene 2 has been investigated using DFT calculations at M06-2X/cc-pVDZ level. Accordingly, the possible reaction pathways and factors that govern selectivity are investigated systematically. Analysis of the calculated results showed that the most favorable cyclization reaction occurs through the [2+4] endo-proximal pathway, which is kinetically and thermodynamically controlled. Moreover, analysis of the global and local reactivity indices correctly explains the source of the experimentally observed regio- and chemoselectivity. The electron localization function (ELF) analysis of some selected points along the IRC profile of the most preferred pathway suggested that the reaction takes place via a two-stage one-step mechanism. NCI topological analysis of the possible pathways of [2+4] cycloaddition reaction of 1-E and 2-Z revealed the roles of the attractive interactions between reaction sites, the weak noncovalent interactions observed in the endo approaches, and the repulsive interactions in the regio- and stereo-selectivity of the reaction.
Keywords: ELF